Women Orbit- easy method for understanding menstrual cycle / Najmi Munirah Abu Bakar, Noorliza Md Yatim and Intan Zulaikha Zulkifli - Abu Bakar, Najmi Munirah; Md Yatim, Noorliza; Zulkifli, Intan Zulaikha (Universiti Teknologi MARA, Kedah, 2019)
The innovation produced is a wheel chart called "Women Orbit" to be applied in understanding the menstrual cycle of a woman. This product is based on the statement of problems faced by women where it was discovered that some have yet to understand their menstrual cycle and the changes that occur within them each month. Before the innovation was introduced, a questionnaire was distributed to the samples to determine the women’s understanding of their menstrual cycle and it was found that the number of women (samples) who did not understand their menstrual cycle were many. The findings also showed that most women were still not able to determine their fertile time and were unaware of the physical and emotional changes that would occur every month. Therefore, "Women Orbit" is produced to facilitate the understanding of women’s menstrual cycle. Through "Women Orbit", the samples can understand and determine the number of days in their menstrual cycle, their fertile time and the changes that take place in their body system throughout the month. Also included are some easy tips for women to apply throughout their menstrual cycle. "Women Orbit" only requires 2 chart cards showing the date for each month and the number of days in the menstrual cycle. It also includes hormonal, emotional, physical and other changes that occur. The wheel chart can be moved on the first day of the first menstruation and the whole changes that occur in women every month will be identified and understood. The total cost required to produce the chart is between RM20 to RM25. The product is also interactive, attractive and portable because of its small size and low cost. With "Women Orbit", women can identify menstrual cycle hormones throughout the month, determine the fertile time (as a family planning method), identify menstrual cycles in the next month and understand the emotional and physical changes that occur throughout the month. The positive impact of this innovation is expected to help and benefit more women in understanding their body system better.